Caracterização do óbito neonatal tardio em uma população de near miss neonatal - Bispo, Luís Fabiano Passos (2017)
Neonatal mortality remains one of the greatest challenges facing public health. Brazil has achieved the goal of reducing child mortality by two thirds, but still has high rates of neonatal deaths. The concept of neonatal near miss (NMN) has been shown to be a useful tool to evaluate the quality of neonatal health care and to point out ways to reduce mortality in the first month of life. A cross-sectional study was carried out nested in a cohort study at a high risk maternity hospital in Aracaju, Sergipe, Brazil, in which cases of NMN were identified and data on gestation and delivery were collected through interviews and medical records. A subsequent online consultation was made to identify late neonatal deaths among NMN cases. A total of 5,408 records were analyzed and 235 cases of NMN were identified, of which 12 died in the late neonatal period. The results point to shortcomings in maternal and child healthcare and to the need for improvements in public policies aimed at pregnant women and their newborns.